The prevalence and impact of lysogeny among oral isolates of Enterococcus faecalis. Issue 1 (1st January 2019) - Stevens, Roy H.; Zhang, Hongming; Sedgley, Christine; Bergman, Adam; Manda, Anil Reddy
ABSTRACT: Bacterial phenotypic properties are frequently influenced by the uptake of extrachromosomal genetic elements, such as plasmids and bacteriophage genomes. Such modifications can result in enhanced pathogenicity due to toxin production, increased toxin release, altered antigenicity, and resistance to antibiotics. In the case of bacteriophages, the phage genome can stably integrate into the bacterial chromosome as a prophage, to produce a lysogenic cell. Oral enterococcal strains have been isolated from subgingival plaque and the root canals of endodontically-treated teeth that have failed to heal. Previously, we isolated a bacteriophage, phage ɸEf11, induced from a lysogenic Enterococcus faecalis strain recovered from the root canal of a failed endodontic case. PCR analysis using phage ɸEf11-specific oligonucleotide primers, disclosed that lysogens containing ɸEf11 prophages were commonly found among oral E. faecalis strains, being detected in 19 of 61 (31%) strains examined. Furthermore, in comparison to an isogenic cured strain, cultures of a lysogen harboring an ɸEf11 prophage exhibited altered phenotypic characteristics, such as increased persistence at high density, enhanced biofilm formation, and resistance to a bacteriophage lytic enzyme. From these results we conclude that lysogeny is common among oral E. faecalis strains, and that it alters properties of the lysogenic cell.